EFFECT OF SACCHAROMYCES CERVISIAE AND LACTOBACILLUS ACIDOPHILUS ON BIOCHEMICAL PARAMETERS OF BARBARI KIDS - Singh, Shiv Pratap; Jain, A.; Roy, Biswajit; Lakhani, G.P (Indian Journal of Animal Production and Management, 2017)
The present study was conducted on Barbari kids to assess the effect of probiotics supplementation onbiochemical parameters. A total 18 Barbari kids were selected and randomly distributed in three groups. The1st group (T1, n=6) was kept control fed (basal ration) without supplementation, the group 2nd (T2, n=6) wassupplemented with Lactobacillus acidophillus @ 2g/animal/day and group 3rd (T3, n=6) was supplementedwith Saccharomyces cerevisiae @ 2g/animal/day. Higher serum blood glucose, total protein and albuminlevel was observed at monthly interval in probiotics supplemented group as compared to unsupplementedgroup. Lower serum cholesterol level was observed in supplemented group T2 and T3 as compared tocontrol group T1.